Albacillium hingganense gen. et sp. nov. (Clavicipitaceae) from forest litters in Northeast China - Ding, Mengmeng; Li, Yupeng; Bai, Yang; Gai, Pingzhuo; Wang, Jian; Jiang, Zizhu; Hu, Yanfeng; Xu, Lijian (Phytotaxa, 2024)
Albacillium hingganense gen. et sp. nov. was isolated from forest litter in Northeast China. This new species characterized by combining its morphological features with a multi-gene (ITS, LSU, rpb1, rpb2, SSU, and tef1) phylogenetic analysis including its related taxa from Clavicipitaceae, Cordycipitaceae, Ophiocordycipitaceae, and a previously unresolved genus Chlorocillium (Hypocreales incertae sedis). According the multi-gene phylogenetic analysis, Albacillium and Chlorocillium formed a monophyletic group that was basal to the Clavicipitaceae. It implied that Albacillium and Chlorocillium belong to Clavicipitaceae. Albacillium hingganense is morphologically distinct from Chlorocillium and its similar taxa by having conidia arranged in mucoid globose heads at the apices of the phialides arising from aerial hyphae.